Laser Panorama in Dentistry in the international year of light - Gonçalves, Sergio Eduardo de Paiva; Azevedo, Luciane Hiramatsu; Ribeiro, Martha Simões; Eduardo, Carlos de Paula (Brazilian Dental Science, 2015)
.